VD_FINDINFO HC / 2014 / 953 vom 28. August 2014 - VD Tribunal cantonal (2014)
PACTE SUCCESSORAL DE RENONCIATION, INVENTAIRE, SUCCESSION, HÉRITIER, EXHÉRÉDATION | 495 CC, 553 CC, 104 CDPJ, 109 al. 3 CDPJ, 111 CDPJ, 117 CDPJ